Academic Librarians at the Table - Bargaining for Parity - Kandiuk, Mary (In Solidarity: Academic Librarian Labour Activism and Union Participation in Canada, 2014)
"[Examines] the role of collective bargaining with respect to improving terms and conditions of employment and the issues and challenges experienced by librarians as members of minority groups within faculty associations." – Editors' introduction.
Keywords: Academic librarians; Canada; Collective bargaining; Faculty status; Labor Unions; Librarians' unions; Library employees